ChemInform Abstract: Metal Free, I2‐Catalyzed [3 + 1 + 1] Cycloaddition Reactions to Synthesize 1, 2, 4‐Trisubstituted Imidazoles. Issue 9 (February 2016) - Tang, Dong; Guo, Xin; Wang, Yu; Wang, Jing; Li, Jihui; Huang, Qiangwei; Chen, Baohua
Abstract: An operationally simple and economical one‐pot procedure is developed for the three‐component reaction of α‐amino carbonyl compounds, aldehydes, and ammonium acetate to afford the title imidazoles.